Coupled Effect of Carbon Nanotubes and Crushing on Shear Strength and Compression of Calcareous Sand Seeped by Colloidal Silica. (12th August 2022) - Jin, Weifeng; Tao, Ying; Cheng, Rongzhong
Abstract : Colloidal silica, which has a low viscosity, can seep quickly through sand and subsequently form silica gel to stabilize the sand. The addition of carbon nanotubes can improve the strength of the sand-gel composite. However, previous literature has not investigated the coupled effect of carbon nanotubes and sand crushing on the strength and compression of colloidal-silica-stabilized calcareous sand. So we prepared 86 specimens with 2 different concentrations of colloidal silica and 9 different contents of carbon nanotubes. Then, we performed triaxial shearing and isotropic compression tests based on the triaxial system. The test results show the following: (1) The same carbon nanotube content at the higher concentration of colloidal silica results in higher shear strength, but increasing crushing makes the shear strengths, respectively, caused by 10 wt% and 40 wt% colloidal silica dispersed with carbon nanotubes tend to be the same. (2) The optimal content of carbon nanotubes, which leads to the maximum shear strength, is distributed differently in different concentrations of colloidal silica; i.e., as crushing increases, the optimal carbon nanotube content drifts from 0.03 wt% to 0.10 wt% in 10 wt% colloidal silica, while 40 wt% colloidal silica stabilizes the optimal carbon nanotube content around 0.08 wt%. (3) Compared with carbon nanotubes in 10 wt % colloidal silica, carbon nanotubes in 40 wt% colloidal silica cause higher cohesion rather than internal friction angle, which is the mechanism of higher shear strength at higher colloidal silica concentration with the same carbon nanotube content. (4) For isotropic compression, minimal compression is caused by 40 wt% colloidal silica plus 0.1 wt% carbon nanotubes.